Differences between mates at the TLR1Lb locus are associated with lower reproductive success in a long-lived seabird - Marianne Gousy-Leblanc; Thomas Merkling; Lila Colston-Nepali; Emma Lachance Linklater; Kyle H. Elliott; Vicki L. Friesen (Scientific Reports)
Abstract Genetic diversity can influence fitness components such as survival and reproductive success. Yet the association between genetic diversity and fitness based on neutral loci is sometime very weak and inconsistent, with relationships varying among taxa due to confounding effects of population demography and life history. Fitness-diversity relationships are likely to be stronger and more consistent for genes known to influence phenotypic traits, such as immunity-related genes, and may also depend on the genetic differences between breeding partners. We recorded breeding success of individuals and breeding pairs over 20 years to evaluate the relationships between reproductive success and both neutral genetic variation (using 7,830 single nucleotide polymorphisms) and functional variation (four toll-like receptor [TLRs] loci) with reproductive success in thick-billed murres (Uria lomvia). Individual genetic diversity (both neutral and functional) was unrelated to reproductive success, but surprisingly, successful multi-year reproductive success decreased with the genetic difference between breeding partners at TLR1Lb. This result may be due to an advantage of specific alleles at TLR1Lb. This study is one of few addressing both individual genetic variation and genetic similarity between mates at both neutral and functional variation in a long-lived bird.